A retrospective cohort study of the utility of the modified early warning score for interfacility transfer of patients with traumatic injury. Issue 5 (9th May 2017) - Salottolo, Kristin; Carrick, Matthew; Johnson, Jacob; Gamber, Mark; Bar-Or, David
Abstract : Objective: The modified early warning score (MEWS) is a 'track and trigger' score using routine physiological vital signs. The objective is to determine if the pretransfer MEWS can be used for predicting outcomes in trauma patients requiring interfacility transfer to higher levels of care. Design, setting and participants: Retrospective study of consecutively transferred trauma patients into a level-II trauma centre from 2013 to 2014. Interventions: None. Outcome measures: Mortality, intensive care unit (ICU) admission, operative procedure, MEWS deterioration in-transit, air transport interfacility, secondary overtriage (low injury severity score (ISS) <10, LOS<1 day, discharged home) and severe injury (ISS ≥16). The association between the pretransfer MEWS and outcomes were analysed with Cochran-Armitage trend tests, receiver operator characteristic (ROC) curves and univariate logistic regression. Results: There were 587 transferred patients; outcomes were reported in 339 patients with complete data on all five vital signs used to calculate the MEWS. The MEWS ranged from 0 to 9 (median of 1). There was a significant linear relationship between MEWS and study outcomes, especially mortality, ICU admission, air medical transport and severe injury (p<0.001 for all). A threshold score ≥4 was identified by ROC analysis; 11.2% of patients had MEWS ≥4. Outcomes were significantly worse in patients with MEWS ≥4 versus <4: mortality (26.2% vs 3.0%, OR=11.59, p<0.001); ICU admission (73.7% vs 47.2%, OR=3.14, p=0.003); air transfer (42.1% vs 15.6%, OR=3.93, p<0.001) and severe injury (59.5% vs 27.2%, OR=3.9, p<0.001). The MEWS was not associated with surgery, in-transit MEWS deterioration or secondary overtriage. Conclusion: Pretransfer MEWS ≥4 may be used by the receiving facility for predicting injury severity, mortality, air transport and ICU resource use. In the interfacility transport setting, the MEWS may be useful for identifying patients with less obvious need for transfer or requiring more expeditious transfer.